2003
DOI: 10.1007/s00249-003-0314-y
|View full text |Cite
|
Sign up to set email alerts
|

Estimating domain orientation of two human antibody IgG4 chimeras by crystallohydrodynamics

Abstract: A modified crystallohydrodynamic approach introduced in 2001 is applied to two human IgG4 constructs from mouse IgG1. The constructs were point mutants of the chimeric antibody molecule cB72.3(gamma4): cB72.3(gamma4A), devoid of inter-chain disulfide bridging, and cB72.3(gamma4P), which has full inter-chain bridging. As before, the known crystallographic structures for the Fab and Fc domains were combined with the measured translational frictional ratios to obtain an estimate for the apparent time-averaged hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…A major monomer peak was observed at s 20, w 0 values of 6.8 S for IgG4(Ser 222 ) and 6.6 S for IgG4(Pro 222 ). These s 20, w 0 values are consistent with the range of values (6.2–6.9 S) reported previously for human IgG4 (20, 4548). Accordingly both IgG4(Ser 222 ) and IgG4(Pro 222 ) were predominantly monomeric in solution and were accompanied by a minor dimer peak.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A major monomer peak was observed at s 20, w 0 values of 6.8 S for IgG4(Ser 222 ) and 6.6 S for IgG4(Pro 222 ). These s 20, w 0 values are consistent with the range of values (6.2–6.9 S) reported previously for human IgG4 (20, 4548). Accordingly both IgG4(Ser 222 ) and IgG4(Pro 222 ) were predominantly monomeric in solution and were accompanied by a minor dimer peak.…”
Section: Resultssupporting
confidence: 92%
“…1). In contrast, earlier studies reported few scattering and ultracentrifugation runs, which limited the evaluation of potential buffer-dependent IgG4 conformations (4548). …”
Section: Discussionmentioning
confidence: 95%
“…Obviously, many classes of molecule cannot be reasonably represented by a smooth symmetrical shape—antibodies are a good example—this type of whole-body modelling is not applicable and bead-approaches need to be employed. Even here, however, ellipsoidal representations of the major domains (Fab, Fc) have helped in the bead modelling of the intact assembly (Carrasco et al 1999, 2001; Longman et al 2003; Lu et al 2006, 2007). …”
Section: Whole Body Models—the Ellips Suite Of Algorithmsmentioning
confidence: 99%
“…They are especially useful for the characterization of antibodies, antibody aggregates, and complexes because obtaining the full-length structures of these large proteins at the atomic-level is difficult if solely based on experimental approaches. Crystallohydrodynamics modeling was used to determine IgG domain orientation and solution conformation [30,31]. Using molecular dynamics simulation, an all-atom model for trastuzumab was established for representative structure in aqueous solution from the crystal structures of antibody fragments [18].…”
Section: Introductionmentioning
confidence: 99%